Head-tail patterning of the vertebrate embryo: one, two or many unresolved problems? - Stern, Claudio D. (2006)
When, where and how is the head-tail axis of the embryo set up during development? These are such fundamental and intensely studied questions that one might expect them to have been answered long ago. Not so; we still understand very little about the cellular or molecular mechanisms that lead to the orderly arrangement of body elements along the head-tail axis in vertebrates. In this paper, we outline some of the major outstanding problems and controversies and try to identify some reasons why it has been so difficult to resolve this important issue.